Exploring the Bone Mineral Density of Health Professionals of Medical College by Using Calcaneal Quantitative Ultrasound - Shamsu Uddin, Abu Muhammad; Rahman, Hafizur; Barua, Shangkar; Alam, Mohammed Nurul; Amin, Umme Salma; Hussain, Md Farhad; Ali, Md Ayub (Journal of Medicine, 2023)
Background: Osteoporosis, an important cause of fracture in Bangladesh is a highly unrecognized and unaddressed issue among health professionals. Osteoporosis means low bone mineral density (BMD) and screening is not done routinely to diagnose it. Moreover, the prevalence of low BMD among Health professionals in the country is not well known. To prevent osteoporosis-induced fracture it demands more attention to early detection, prevention, and treatment. Objectives: The present study was carried out to assess the bone mineral status of health professionals of Cox’s Bazar medical college and also to find out the correlation with age, sex, Vitamin D, calcium supplementation, and physical activity by using quantitative ultrasound (QUS) of the calcaneus. Materials and Method: This is a descriptive, cross-sectional study that has been done at Cox’s Bazar Medical College. Result: The total number of participants was 267 which were screened by using a calcaneal ultrasound heel bone densitometer. Among them 190 were female and 77 were male. The majority of the health professionals 237(88.76%) were below 45 years. Mostly, 194(72.66%) participants had normal BMD, 73(27.34%) participants were in osteopenia and none of them were osteoporotic. Among those above 45 years old study people, nearly half 14(46.67%) were osteopenic, and for ages below 45 years of health professionals, only 59(24.89%) were osteopenic. Out of 77 male participants, 15(19.48%) were osteopenic and out of 190 female participants, 58(30.53%) were osteopenic. Out of the total 267 study people, 81(30.34%) agreed to take calcium and vitamin-D supplementation with significant p-value = 0.003 whereas 32(39.51%) participants were in the osteopenic stage and 49(60.49%) had healthy bony status. The number of using Calcium and vitamin-D supplementation was high, which may be due to positive answers from particular participants like the elderly and health care supporting staff. In our study 120(44.94%) participants did exercise but mostly irregularly, and 147(55.06%) did not do exercise. Out of 120(44.94%) participants doing regular exercise 37(30.83%) were osteopenic and the rest of 83 (69.17%) health professionals were in normal BMD. Conclusion: Among the health care professionals, osteopenia is not uncommon and regular exercise practice and rational Calcium and vitamin-D supplementation may be preventive for osteoporosis. J MEDICINE 2023; 24(2): 131-134